Towards building an educational system free of scientific corruption (Applied study in a sample of colleges of higher education in Iraq within the framework of the government program and the directions of the Supreme Council for Combating Corruption) - الفضل مؤيد عبد الحسين; كاظم هديل مهدي (Journal of Economics and Administrative Sciences, 2020)
Nations are developed with education and knowledge that raise the status of society in its various segments, beyond that it leads to underdevelopment and deterioration in various sectors, whether economic, health, social, etc. If we considered the general name of The ministry of Education & Scientific Studies, then the second part seems to be not functioning, since scientific research has no material allocation and remains based on the material potential of the university professor. As for the first half of the topic, the reality of the situation reveals problems related to the Holy Trinity of Education which is (Professor - Student - the scientific method) where universities suffer at the present time from this problem, and the situation became worse with the appearance of private universities that operate according to their own agendas. Therefore, this research has been prepared to build an educational system free of scientific corruption (applied study in a sample of colleges of higher education in Iraq within the framework of the government program and the directions of the Supreme Council against Corruption). The researchers followed two methods, the first of which was devoted to presenting the intellectual framework of the study through the use of research and studies related to the subject of the research, while the second dealt with the applied side, which was implemented by preparing a two-part questionnaire, the first part represents information about people from the staff and teaching staff, this part consists of three axes: (Trinity University Education / Program The government program and the orientations of the Supreme Council for Combating Corruption, Postgraduate Studies), A random sample consisting of (63) singles distributed on the headquarters of the Ministry of Higher Education and Scientific Research by (15) questionnaires and Baghdad University / Jadriya by (15) questionnaires and the universities of Kufa and the Middle Euphrates by (18) questionnaires and finally the University of Karbala by (15) questionnaires, and in light of that Data were collected and analyzed and hypotheses tested using the statistical software (spss). The researchers reached a number of conclusions, the most prominent of which is that the triad of higher education (professor-student-curriculum) is still below the level of ambition. The researchers also presented a set of recommendations, the most important of which is the importance given to the essence of the educational process and thus the Trinity known (Professor-student-curriculum) as a basic step in order to stand up to scientific corruption in all its forms.